Foot and mouth disease (FMD) in cattle and buffaloes in two quarantine stations and six selected states of Peninsular Malaysia between 2010 and 2015 - Nik Kamarudin, Nik Nur Fatin Amira (2016)
Foot-and-mouth disease (FMD) is a highly contagious disease of cloven-hoofed animals. Malaysia has been importing live ruminant for domestic demand and this could pose a risk to the local ruminant industry. Movement of FMD infected animals is one of the main factors for outbreaks. The objectives of this study were to determine the seroprevalence of FMD in cattle and buffaloes in Padang Besar (PB) and RantauPanjang (RP) Animal Quarantine Stations from 2010 to 2015, and to describe the outbreaks of FMD in six selected states. The existing data between 2010 and 2015 were reviewed including results from the Enzyme-Linked Immunosorbent Assay (ELISA) 3ABC non-structural protein (NSP) of FMD retrieved from the Regional Veterinary Laboratory Kota Bharu, and outbreaks data extracted from the World Organization for Animal Health Regional Coordination Unit (OIE-RCU) website. Based on the NSP tests, the overall seroprevalence of FMD in quarantine stations was 36.4% (RP: 40.7%, PB: 34.9%) and there was significant difference between both stations (χ2=42.3, df=1, p<0.05). The highest seroprevalence of FMD was recorded in 2011 and the lowest in 2012. There was significant difference for seroprevalence between years (p<0.05). Significantly higher seroprevalence (p<0.05) were also found in cattle than buffaloes (36.6%, 30.7%, respectively), and males than females (39.1%, 30.4%, respectively). The total number of outbreaks of FMD in the northern states of Peninsular Malaysia from 2010 to 2015 was 69 (2010 - 19, 2015 - 4). Terengganu recorded the highest (26) number of outbreaks while the lowest was in Perlis (1). Monthly FMD outbreak occurrence was the highest in September. Virus serotype O and serotype A were the main cause of outbreaks in the selected states of Peninsular Malaysia. The findings showed that FMD is endemic in Malaysia and control strategies need to be improved.